Implementation of international treatment guidelines in the treatment of schizophrenia : a study of the effects of an evidence-based seminar on the knowledge and treatment habits of a sample of international psychiatrists - Joubert, Andre Francois (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DMed (Psychiatry))--University of Stellenbosch, 2007.